Escape from the ghetto : a story of survival and resilience in World War II - Carr, John, 1949-; Herszman, Chaim (Pegasus Books, 2022)
"In early 1940 Chaim Herszman was locked in to the Lódz Ghetto in Poland. Hungry, fearless, and determined, Chaim goes on scavenging missions outside the wire fence--where one day he is forced to kill a Nazi guard to protect his secret. That moment changes the course of his life and sets him on an unbelievable adventure across enemy lines. Chaim avoids grenade and rifle fire on the Russian border, shelters with a German family in the Rhineland, falls in love in occupied France, is captured on a mountain pass in Spain, gets interrogated as a potential Nazi spy in Britain, and eventually fights for everything he believes in as part of the British Army. He protects his life by posing as an Aryan boy with a crucifix around his neck, and fights for his life through terrible and astonishing circumstances. Escape from the Ghetto is about a normal boy who faced extermination by the Nazis in the ghetto and a Nazi death camp, and the extraordinary life he led in avoiding that fate. It's a bittersweet story about epic hope, beauty amidst horror, and the triumph of the human spirit" --